Les paradoxes des droits reproductifs au Brésil: avortement et stérilisation féminine - Scavone, Lucila; Bateman, Simone; Le Doaré, Hélène (Cahiers du Genre, 1999)
Cet article rend compte du débat mené au Brésil autour des droits reproductifs et souligne les avancées et les contradictions particulières de deux problèmes que rencontrent actuellement les femmes brésiliennes : la stérilisation et la pratique illégale de l’avortement. Il met en évidence que la pratique généralisée de la stérilisation féminine et le nombre des avortements clandestins, qui représentent un risque pour la santé des femmes, révèlent les carences de la politique de la santé sur le plan des choix reproductifs et de la politique de contrôle démographique. Il montre les diverses orientations prises par ce débat à la fin des années quatre-vingt-dix et la nécessité de se réapproprier sa dynamique de transformation sociale.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du sud; approches et analyses; brésil; corps; cours; discipline; discours dominant; droits des femmes*; justice reproductive; maternité; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail reproductif

America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

II. Une perspective féministe dans l’histoire des congrégations de femmes - Dumont, Micheline (Études d'histoire religieuse, 1990)
Keywords: 1900-1999; 1960-1969; 1970-1979; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; discours dominant; his4550; histoire; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; sciences humaines; systèmes d'oppressions; thématiques; travail